Functional characterization of Rasd1 : a novel interaction between Rasd1 and Ear2 (NR2F6) is involved in the regulation of renin transcription - Tan, Jen Jen (2012)
Rasd1 (Ras dexamethasone-induced 1), also known as Dexras1 and activator of G proteins signaling 1 (AGS1), belongs to the Ras superfamily of GTPase. The characteristic GTP binding and hydrolysis properties of Ras proteins render Rasd1 extremely important in numerous signaling pathways and physiological processes. Rasd1 is known to regulate cell growth, cell differentiation and cell death. Rasd1 is also involved in the regulation of neuronal iron homeostasis and circadian timings. Rasd1 was first identified in 1998. Although a few of its downstream targets have been identified, its related signaling pathways have not been definitively established. This project is focused on the functional characterization of Rasd1. To identify potential proteins that interact with Rasd1, I performed yeast two-hybrid assays using Rasd1 as bait against a mouse brain cDNA library. Any promising proteins that interact with Rasd1 will be studied further to elucidate the functional significance of the interaction and to resolve the molecular mechanisms and signaling pathways involved. Identification of Rasd1 interaction partners will provide important functional link on which future translational research will be based. Yeast two-hybrid analysis revealed several proteins that specifically interact with Rasd1. I chose to further examine the functional significance of the interaction between Rasd1 and erb-A related 2 (Ear2), also known as nuclear receptor subfamily 2, group F, member 6 (Nr2f6), as Ear2 produced three independent hits in the yeast two-hybrid assay, and both Rasd1 and Ear2 are known to be involved in the regulation of the circadian rhythm and in neurological developments. It was confirmed that Rasd1 and Ear2 interact in vitro and form an endogenous complex in living cells. Ear2 is a known repressor of renin transcription. It was demonstrated that Rasd1 is able to alleviate both retinoic dependent and independent Ear2-mediated repression of renin gene transcription. This activity was observed in endogenous renin promoter and transfected renin promoter constructs. The knockdown of Rasd1 by RNAi caused a further suppression in the Ear2-mediated repression of renin promoter activity. Moreover, Ear2 interacted with Rasd1 via its ligand binding domain, and that both the DNA binding and ligand binding domains of Ear2 were crucial in Rasd1- and Ear2-mediated renin gene transcription. In addition, confocal studies demonstrated that wild type Rasd1 and its constitutively active Rasd1 mutant, Rasd1[A178V], were able to alter the nuclear-cytoplasmic distribution of Ear2. When co-transfected, a significant